Mechano-stimulated equilibration of gold nanoparticles on sapphire. (October 2015) - Kovalenko, O.; Rabkin, E.
Graphical abstract: Abstract: We present a new method for equilibration of faceted nanoparticles obtained by solid state agglomeration (dewetting) of metal thin films. The method relies on crystalline defects introduced in the particles by the atomic force microscopy-based indentation and tapping. The developed method was employed for statistically based determination of the Au 1 1 1/sapphire 0 0 0 1 interfacial energy, with the result (2.11 ± 0.08 J/m 2 ) being in good agreement with the values reported in the literature.